A Case of Achalasia Presented with Cardiopulmonary Arrest. (24th December 2012) - Altintoprak, Fatih; Degirmenci, Bumin; Dikicier, Enis; Cakmak, Guner; Kivilcim, Taner; Yalkin, Omer; Akbulut, Gokhan; Dilek, Osman Nuri
Abstract : Achalasia is a rare disorder characterised by obstruction of the distal oesophagus and subsequent dilation of the proximal oesophagus. Patients generally complain of gastrointestinal symptoms; however, pulmonary symptoms and complications may also occur. A 35-year-old woman was brought to our emergency service complaining of sudden-onset dyspnea that started 15 minutes earlier during dinner. She suffered a cardiopulmonary arrest due to aspiration 5 minutes after being admitted to the emergency room and was intubated. Thoracic computed tomography examination showed that her oesophagus was filled with undigested food. Heller cardiomyotomy and Dor fundoplication was performed via laparotomy with the diagnosis of primary achalasia, and she was discharged as uneventful on the 5th postoperative day.